Computer-Based National Assessment Service at the Junior High School Level in North Aceh Regency - Syamsuddin; Ferizaldi; Hasyem, Muhammad (Program Magister Administrasi Publik, 2025)
This study examines education administration services using the Basic Education Data (Dapodik) application whose services have not been able to carry out the Computer-Based National Assessment simultaneously on September 19-22, 2023. The purpose of the research is to analyze the service standards of the Computer-Based National Assessment (ANBK) using the Application of Basic Education Data (Dapodik) in Junior High Schools (SMP) in North Aceh district related to facilities and infrastructure. The obstacles analyzed in the implementation of this Assessment are related to internal and external interactions. The theoretical perspective used is the theory of public service standards (Alfianto, 2020). Barriers to public servants (Atep, 2021). The research method used is descriptive qualitative research, with data collection techniques through observation, interviews, and documentation. The results of the study related to facilities show that education administration services using Basic Education Data in the simultaneous Computer-Based National Assessment (ANBK) service are not optimal because the facilities owned by schools with passenger status are still using semi-online servers. Regarding obstacles related to internal and external employee interaction, serious things have not been found that can hinder the service of the Computer-Based National Academies in North Aceh.